PENGARUH PENGELOLAAN BANK SAMPAH TERHADAP SIKAP EKONOMI HIJAU NASABAH BANK SAMPAH ROSELLA KECAMATAN PONTIANAK SELATAN - Fikri Abdillah; Nuraini Asriati; Warneri Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine how much influence the management of the Waste Bank has on the green economy attitude of the customers of the Rosella Garbage Bank, South Pontianak District. The assessment approach uses a quantitative approach with the type of ex post facto research. The data used are primary data. The sample studied was 58 respondents obtained from the purposive sampling technique which is an active customer of the Rosella Garbage Bank, South Pontianak District. Collecting data using indirect communication techniques, observation, and documentary studies. The data were processed using simple linear regression analysis. The results of the study found that: 1) The management carried out by the waste bank manager was very good at 78%; 2) The green economic attitude of the Rosella Waste Bank customers as a whole shows it is included in the "Very High" category at 83.1%; 3) Waste bank management has a positive and significant influence on the green economy attitude of waste bank customers by 53.4% with a t count of 8.005 while the t table at 5% significance is 2.003 which means Ha is accepted. So in conclusion, there is an ef ect of waste bank management on the green economy attitude of the customers of the Rosella Garbage Bank, South Pontianak District, amounting to 53.4%, while the remaining 46.6% is influenced by other factors not examined by researchers.Keywords: Waste Bank, Green Economy Attitude, Customers.